Political developments in Sri Lanka (1945-1948) and the British position on it - Al-Fahad , Assistant Prof. Maher Chasib Hatem (Thi Qar Arts Journal, 2022)
.This study deals with the topic ( Political Developments in Sri Lanka 1945-1948 and the British position on it), During this era, Sri Lanka witnessed important political and constitutional changes that had a major role in achieving national independence, Although it was within the British Commonwealth system, but it got rid of largely from the restrictions of British colonialism. During this era, there was clear cooperation between most of the leaders of the national movement on the one hand, and the British authorities on the other .This British-Sri Lankan cooperation has resulted in several results, the most important of which is a gradual progress in the political and constitutional status of Sri Lanka, On the basis of which Sri Lanka was transformed from a colony administered directly by the British Governor-General in Sri Lanka to a country that enjoys a large degree of independence, Its affairs are administered by the Sri Lankan Prime Minister supported by a Legislative National Assembly elected by the Sri Lankan people. This cooperation also led to a major shift in the course of the political process in Sri Lanka. For the first time in the country’s history, political parties with different ideologies and partisan approaches appeared. To organize the masses and work to guide them politically. During this stage, the country witnessed the drafting of the first constitution in the country’s history. The process of drafting and approving it went through several stages until it took its final form in 1946. This stage also marked the emergence of the first national legislative assembly elected by the Sri Lankan people. And in which the right to participate is granted to both men and women, and Sri Lanka may be the first British colony in Asia to hold elections of this kind.